Inevitability of Translation and Indeterminacy at Home - Hossein Shaqaqi (حکمت و فلسفه, 2020)
"Indeterminacy begins at home" is the most important result of Quine's arguments in defense of "translation indeterminacy". This conclusion, which is also supported by Davidson, and hence we will call it the Quinnie-Davidson thesis, indicates a lack of definition of meaning in the mother tongue. Hans Gluck, who likens this thesis to the "inevitability of translation" thesis in Gadamer's philosophical hermeneutics, criticizes Quine-Davidson's thesis and does not consider it defensible. Here, first, by reviewing Quinnie-Davidson's thesis as well as Gadamer, I will confirm Glock's alleged similarity, and secondly, in refuting Glock's criticisms, I will try to defend the Quine-Davidson thesis by reviewing the similarity and balance between the position of Quinn's root translator from one hand, and Quine's account of the situation of the child on the verge of learning the mother tongue, on the other hand.